Gallatin : America's Swiss Founding Father. - Dungan, Nicholas (NYU Press, 2010)
You won't find his portrait on our currency anymore and his signature isn't penned on the Constitution, but former statesman Albert Gallatin (1761-1849) contributed immeasurably to the formation of America. Gallatin was the first president of the council of New York University and his name lives on at NYU's Gallatin School of Individualized Study, so it is with pride that New York University Press and the Swiss Confederation publish this new biography of Gallatin. Gallatin's story is the opposite of the classic American immigrant tale. Born in Geneva, the product of an old and noble family and.